PENGARUH PIJAT OKETANI TERHADAP PRODUKSI ASI PADA IBU NIFAS DI KLINIK PRATAMA FITRI ASIH KEC.PATUMBAK TAHUN 2025 - Natalia, Kristin -; Sinuhaji, Esterlita (JURNAL ILMIAH DHDT - KEBIDANAN, 2025)
Introduction: Optimal breast milk production is essential to support the growth and development, especially in the early years of life. However, many postpartum mothers experience problems with breast milk production, which can be caused by various factors such as stress, lack of nutrition, and lack knowledge regarding breast care techniques. Oketani massage is a non-pharmacological method that is able to increase prolactin hormone, and stimulate oxytocin hormone and make the breasts smoother and more elastic. Research Objective: This study aims to determine the effect of Oketani massage on breast milk production in postpartum mothers. The research design is a Quasi-Experiment study with one grub pretest-postest design. Sampling was conducted using total sampling with 15 respondents. The research instrument used an observation sheet to measure breast milk production through indicators such as breastfeeding frequency, the number of times the baby urinates, the baby's calmness after breastfeeding, and the baby's weight gain. Research Results: The results obtained from the Paired Sample t-Test obtained a p-value of 0.008, where p < α (0.05), so it can be concluded that Ho is rejected and Ha is accepting. Conclusion: It can be concluded that Oketani massage has an effect on breast milk production in postpartum mothers at Fitri Asih Primary Clinic, Kec.Patumbak. Therefore, it is recommended that healthcare workers and postpartum mothers apply Oketani massage as a non-pharmacological method to increase breast milk production in postpartum mothers.